2015
DOI: 10.5897/ajar2015.10327
|View full text |Cite
|
Sign up to set email alerts
|

Fertiliser subsidy effects on fertiliser use in the northern region of Ghana

Abstract: This study examines the effect of fertiliser subsidy on application rates of fertiliser among maize farmers in Northern Region. The study uses cross-sectional data from 301 households in the northern region of Ghana. The Probit and Tobit models were respectively used to analyse the determinants of participation in the subsidy programme and the effect of participation on fertiliser application rates. The results of the study show that farm size, price of the subsidised fertiliser, distance to input dealers, amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 16 publications
6
14
1
Order By: Relevance
“…This means that less distance from farm to market centres increases the probability of farmers to benefit/participate in subsidy program. This result agrees with Imoru and Ayamga (2015), but in contrary with Zhou et al (2010) who found that farm distance to market have negative effect on intensity of fertiliser usage.…”
Section: Determinants Of Participation In Fertilizer Subsidy Programsupporting
confidence: 89%
See 2 more Smart Citations
“…This means that less distance from farm to market centres increases the probability of farmers to benefit/participate in subsidy program. This result agrees with Imoru and Ayamga (2015), but in contrary with Zhou et al (2010) who found that farm distance to market have negative effect on intensity of fertiliser usage.…”
Section: Determinants Of Participation In Fertilizer Subsidy Programsupporting
confidence: 89%
“…The positive and significant relationship between age and participation meant that older farmers were more likely to have benefited or participated in the fertilizer subsidy program. This result is corroborating with Chirwa et al (2011), and Imoru and Ayamga (2015), but in contrary with the findings of Martey et al (2013), and Ragasa and Chapoto (2017).…”
Section: Determinants Of Participation In Fertilizer Subsidy Programsupporting
confidence: 88%
See 1 more Smart Citation
“…Many studies have been conducted on impacts of fertilizer subsidy (Vondolia et al, 2021;Tsiboe et al, 2021;Andani et al, 2020;Imoru and Ayamga, 2015;Fearon et al, 2015;Sianjase and Seshamani, 2013;Chibwana et al, 2012;Banful, 2011). These studies identified mixed evidence on impacts of fertilizer subsidy (for instance, see Warr and Yusuf (2014), Druilhe and Barreiro-Hurl e (2012), Dorward and Chirwa (2011)).…”
Section: Ijppm 731mentioning
confidence: 99%
“…Fertilizer subsidy targets the reduction of market prices of fertilizer to enhance demand and application of fertilizer and agricultural productivity (Fearon et al, 2015;Imoru and Ayamga, 2015). According to Vondolia et al (2021), Ghanaian farmers who benefitted from fertilizer subsidy applied 45% more fertilizer than non-beneficiaries.…”
Section: Introductionmentioning
confidence: 99%